(3TQM GdNQjOI GdHgjIs - (3GdnYnOhj, CHh GdHQcGJ, GdnqOrQpOjQ, CMeO Hf eMeO Hf CMeO (B, (3J (B1201 (3g`s ((3Ndjd Hf CHh GdSYhO GdYLeGhj GdeGdcjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj fhQ bdhHfG HeYQaI YbGjO GdJhMjO CeG HYO agPG TQM dWja Ydi ebOeJj GdeSeGI HGdNQjOI GdHgjI GdJj fXeJgG aj GdYbGFO GdJhMjOjI HSe Gddg GdQMef GdQMje Cj Chda EfeG bOQfG GdeJYdbs
(3BNQgG (B:s
(3hdh cGf Hge NUGUI hef jhb TM faSg aChdFc ge GdeadMhf QVj Gddg Yfge hYfG Hge Bejfs
(3fSNJ Yf fSNI GdeDda GdeDQNI SfI (B1177 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 244s
(3eYLe GdeDdajf (B1 / 242s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds